Android Mobile Application for Promotion of Pangandaran Leading Tourism in Augmented Reality Technology - Ady Purna Kurniawan; Vany Octaviany; Danica Rani Intani Putri; Budi Ikhsan; Dimas Adianto (IJAIT (International Journal of Applied Information Technology), 2020)
The use of smartphone devices has become a part of people's lives in finding the information they need, including finding tourist locations that suit their desires. The problem is when tourism site managers cannot keep up with technological developments needed by the community, where most still use conventional paper media marketing methods such as brochures and travel pocketbooks. Therefore, the development of tourism promotion applications is needed to support the marketing of tourist destinations such as in Pangandaran, West Java. This application's development uses the Prototype method, which only focuses on functionality needs, which uses video media that is displayed with Augmented Reality technology. The results of the development of this application can only display 7 (seven) superior tourism location videos in Pangandaran, West Java.